Biotechnology Regulation and Trade - Smyth, Stuart J. author. aut Link
XXI, 275 p. 18 illus.
Keywords: This book discusses the regulatory and trade challenges facing the global adoption of biotechnological products and offers strategies for overcoming these obstacles and moving towards greater global food security. The first section of the book establishes the context of the conflict, discussing the challenges of global governance, international trade, and the history of regulation of genetically modified (GM) crops. In this section, the authors emphasize the shift from exclusively science-based regulation to the more socio-economically focused framework established by the Cartagena Protocol on Biosafety, which was adopted in 2000. The second section of the book provides a snapshot of the current state of international GM crop adoption and regulation, highlighting the US, Canada, and the EU. The final section of the book identifies options for breaking the gridlock of regulation and trade that presently exist. This book adds to the current literature by providing new information about innovative agricultural technologies and encouraging debate by providing an alternative to the narratives espoused by environmental non-governmental organizations. This book will appeal to students of economics, political science, and policy analysis, as well as members of regulatory agencies and agricultural industry firms. .